Expression of the Arginine Regulon of Escherichia coli W: Evidence for a Second Regulatory Gene - Theil, Elizabeth C. (1969)
Effect of the M (modifier) gene of Escherichia coli W on the expression of wild-type structural genes of four arginine biosynthetic enzymes was studied by examining enzyme activity in cell-free extracts of cultures grown in minimal medium and medium containing arginine. The mutant M gene was originally identified as causing arginine-induced synthesis of acetylornithine δ-transaminase in a strain deficient for the enzyme. The strains used in this study received the mutant M gene by recombination. Noncoordinate repression has been demonstrated for two more enzymes of the arginine regulon of E. coli W and the M(−) gene increases the degree of noncoordinate repression for the regulon. Mutation of the M gene results in altered regulation of acetylornithine δ-transaminase, ornithine transcarbamylase, and acetylornithinase. In addition, a decreased growth rate is observed. It is proposed that the M gene is a regulatory gene. A model is presented to explain the data which involves changes in operator-repressor affinity for the structural genes and possibly for the gene controlling arginyl transfer ribonucleic acid synthetase.